THE REFUGEES AREN’T COMING. CURRENT NEEDS IN THE POLISH EDUCATION (TOWARDS EDUCATION FOR PEACE - Roszak, Joanna (Porównania, 2018)
The author of the article emphasizes the need to confront the youth with the theme of “the others” (in an ethnic, national and religious sense). It is associated with a relatively new social and political situation: the intensifying migratory movement. Polish schools should see for themselves the important issue in the context of the escalating humanitarian crisis and global nomadism. During the phase of collecting materials for the paper categorized interviews with teachers, librarians and students of ten schools in Poznań were conducted. The author of article analyzes and interprets the content of textbooks used in teaching the Polish language and literature and proposed projects of topics associated with the theme of refugees. The conclusion of the article is that the most important task for the Polish education, at all levels, appears to be the introduction of education for peace.